(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
“Electronic Governance (e‐Governance) is the application of information& communication technologies to transform the efficiency, effectiveness,transparency and accountability of informational & transactional exchangeswith in government, between govt. & govt. agencies of National, State,Municipal & Local levels, citizen & businesses, and to empower citizensthrough access & use of information”1